1999
DOI: 10.3109/10641959909009612
|View full text |Cite
|
Sign up to set email alerts
|

Are Women with Polycystic Ovary Syndrome at an Increased Risk of Pregnancy-Induced Hypertension and/or Preeclampsia?

Abstract: No major differences with regard to perinatal outcome in pregnant women with and without PCOS were found. An increased risk of hypertensive disorders in the third trimester and during labor was demonstrated in the PCOS group. This suggests that in the antenatal care of women with PCOS, attention should focus on blood pressure in order to reduce the risks of morbidity associated with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 9 publications
4
45
0
1
Order By: Relevance
“…Likewise, logistic regression indicated that women undergoing poor-quality embryo transfer are not at increased risk for pregnancy complications after adjusting for potential confounding factors. A recent meta-analysis indicated a strong relationship between pregnancy complications and PCOS [24]; several studies support this finding [25,26]. Therefore, adverse outcomes are related to assisted reproduction technology, but also patient-related factors [27,28].…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, logistic regression indicated that women undergoing poor-quality embryo transfer are not at increased risk for pregnancy complications after adjusting for potential confounding factors. A recent meta-analysis indicated a strong relationship between pregnancy complications and PCOS [24]; several studies support this finding [25,26]. Therefore, adverse outcomes are related to assisted reproduction technology, but also patient-related factors [27,28].…”
Section: Discussionmentioning
confidence: 86%
“…However, pre-eclampsia was only found to be more frequent in the insulin resistant PCOS women and not in the non-insulin-resistant PCOS group when compared to controls. Earlier reports [8,[13][14][15] have shown hypertensive pregnancy complications to be more frequent in PCOS women than controls. In some of these reports the confounding effect of parity GDM in Insulin-Resistant PCOS Women has not been accounted for [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Fridstrøm et al [8] have recently shown that there were differences in BMI and blood glucose levels during pregnancy between PCOS and control groups. Since the blood glucose levels and birth weights were similar in the two groups the authors concluded that hyperinsulinemia should be of minor importance in terms of pregnancy outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The impact that the syndrome has on human reproduction does not only include anovulatory infertility, but also detrimental effects on oocyte [3][4][5][6] and embryo 7 quality, endometrial receptivity, 8,9 and pregnancy development. 10 Retrospective [11][12][13][14][15] and prospective [16][17][18] noncontrolled data designated PCOS as a risk factor for increased incidence of complications throughout pregnancy. A recent meta-analysis 10 confirmed an increased risk for gestational diabetes mellitus (DM), pre-eclampsia (PE), pregnancyinduced hypertension (PIH), and preterm birth.…”
Section: Introductionmentioning
confidence: 99%